10-year experience in orthotopic heart transplantation in Kuzbass - L. S. Barbarash; O. L. Barbarash; E. V. Grigoriev; D. L. Shukevich; T. B. Pecherina; M. G. Zinets; A. V. Sotnikov; I. K. Khalivopulo; T. S. Golovina; E. M. Kurguzova; A. V. Ivanova; Yu. S. Ignatova; et al. (Вестник трансплантологии и искусственных органов, 2025)
Background. Orthotopic heart transplantation (OHT) is the gold standard treatment for individuals with endstage heart failure (HF), providing the best survival and quality of life. In Russia, the number of OHT procedures and transplantation of other organs have significantly increased in recent years. At the same time, there is lower perioperative mortality and higher survival in the post-OHT long-period.Objective: to analyze OHT outcomes in Kuzbass over a 10-year period.Material and methods. From January 2013 to December 2023, 72 OHTs (36.7% of those included on the heart transplant waiting list (HTWL) over a 10-year period) were performed at the Research Institute for Complex Issues of Cardiovascular Diseases. Recipient median age was 56 [50.5; 61.0] years, which included 61 men and 11 women. Among the etiologic causes of end-stage HF, ischemic cardiomyopathy was predominant in 65.3% (n = 47) of recipients, whereas dilated cardiomyopathy was present in 25% (n = 18) of recipients. Other cardiomyopathies accounted for 9.7% (n = 7).Results. A total of 196 patients with end-stage HF were included in the HTWL over a 10-year period; 74 (37.8%) of these did not live to get a transplant. The waitlist time was 173 days (5.77 months) – which is slightly longer than the average waiting time of 3.9 months for OHT according to data from European registries. Waitlist mortality was 19.6%. The 10-year average in-hospital mortality rates among patients after OHT were 16.7% and 1-year mortality was 15.3%. These rates are consistent with worldwide trends for this high-tech medical care. Cumulative survival at the end of 2023 was 51.4% (36 patients after OHT). Median length of stay in the hospital was 28 days, with 14 days spent in the intensive care unit. Donor heart anoxia time was 112 [85.25; 170.5] minutes, and cardiopulmonary bypass time was 145 [124; 169.5] minutes. Ten patients (13.9%) required extracorporeal membrane oxygenation, while 8.3% of cases required extracorporeal homeostasis correction.Conclusion. The 10 years of successful experience at the Research Institute for Complex Issues of Cardiovascular Diseases validates the need to develop the OHT program in Kuzbass as a gold standard for treating end-stage HF.